Identifikasi Pola Miskonsepsi Siswa pada Konsep Bioteknologi Modern dan Konvensional serta Strategi Remediasinya: Sebuah Tinjauan Literatur - Gea, Sehati; Halawa, Desheriasti; Zai, Masleni; Nazara, Sudieli; Zega, Novelina Andriani (Indo-MathEdu Intellectuals Journal, 2026)
Biotechnology education in secondary schools and universities still faces challenges in the form of high levels of student misconceptions, mainly due to the abstract nature of the material and the rapid development of technology. This study aims to identify common misconceptions in conventional and modern biotechnology material and analyse effective remediation strategies based on previous research findings. The research method used is a systematic literature review, through searching and analysing nationally and internationally accredited journal articles published between 2015 and 2025. The articles analysed were selected based on topic relevance, methodological quality, and relevance of findings. The results of the study show that the most dominant misconceptions arise in the understanding of the concept of anaerobic fermentation, the difference between cloning and IVF, and the impact of genetically modified organisms (GMOs). Remediation strategies that have proven effective include the use of Conceptual Change Text, the application of the Socio-Scientific Issues (SSI) approach, and the use of virtual laboratory simulations to help students reconstruct their understanding of concepts more accurately.